2019
DOI: 10.1016/j.bpj.2019.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Induced Extensional Response Behaviors of Tethered von Willebrand Factor

Abstract: We perform single-molecule flow experiments using confocal microscopy and a microfluidic device for shear rates up to 20,000 s À1 and present results for the shear-induced unraveling and elongation of tethered von Willebrand factor (VWF) multimers. Further, we employ companion Brownian dynamics simulations to help explain details of our experimental observations using a parameterized coarse-grained model of VWF. We show that global conformational changes of tethered VWF can be accurately captured using a relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 70 publications
(125 reference statements)
0
28
0
Order By: Relevance
“… 134 NPSS can change VWF multimers from a globular shape to an elongated rope-like structure. 135 Structural changes of VWF molecule induced by NPSS expose the A2 domain 136 , 137 and promote proteolytic cleavage by ADAMTS-13 and multimeric binding to platelets GP1ba through A1 domain. 138 The VWF-platelet binding also increases proteolytic cleavage by ADAMTS-13.…”
Section: Shear-induced Acquired Von Willebrand Syndrome (Avws)mentioning
confidence: 99%
“… 134 NPSS can change VWF multimers from a globular shape to an elongated rope-like structure. 135 Structural changes of VWF molecule induced by NPSS expose the A2 domain 136 , 137 and promote proteolytic cleavage by ADAMTS-13 and multimeric binding to platelets GP1ba through A1 domain. 138 The VWF-platelet binding also increases proteolytic cleavage by ADAMTS-13.…”
Section: Shear-induced Acquired Von Willebrand Syndrome (Avws)mentioning
confidence: 99%
“…The length of VWF multimers significantly affects their responses to shear. A lower threshold of shear rate is required to extend long VWF multimers ( 52 ). A recent research suggested that tension, but not shear stress, regulates the affinity of VWF for platelet glycoprotein Ibα (GPIbα) ( 53 ).…”
Section: The Von Willebrand Factor and Adamts13mentioning
confidence: 99%
“…The details of the microfluidic device design and fabrication can be found in our previous work with slight modification. 24 In this study, PDMS precursor and curing agent (Dow Corning, MI, USA) were mixed at a 5:1 weight ratio to achieve stiffer channels that resist deformation under the hydrodynamic pressure. The mixture was incubated at 60°C for 4 h to cure fully.…”
Section: Microfluidic Device and Vwf Immobilizationmentioning
confidence: 99%